Nurses' Decisions, Irreducible Uncertainty and Maximizing Nurses' Contribution to Patient Safety - Carl Thompson and Huiqin Yang (Law & Governance, 2015)
[This article was originally published in Healthcare Quarterly, 12 (Special Issue)]  Nurses, like all healthcare professionals, use reasoning and judgment to make decisions. In doing so, they must grapple with irreducible clinical uncertainty. But, in managing uncertainty, the modes of reasoning used should encourage more good than harm. However, the nursing profession considers intuitive reasoning as a mark of the expert. Consequently, nurses are predominantly taught to handle uncertainty intuitively. Information-seeking behaviour is rare. This is problematic for two reasons: (1) intuitive decision-making is prone to reasoning biases and (2) mechanisms to judge nurses' decision-making rarely use intuitive responses themselves as the basis for scrutiny. In addition, when we evaluate nurses' decision-making in the context of problems such as time pressure, a less-than-optimistic picture emerges. However, this type of examination is a necessary first step in maximizing the contribution of nurses to patient safety.
Keywords: Nurses, patient safety, decision making